Cross-reactivity of antibodies to different rumen methanogens demonstrated using immunomagnetic capture technology - Khanum, Sofia; Roberts, Joanna M.; Heathcott, Rosemary W.; Bagley, Stefanie; Wilson, Tania; Gupta, Sandeep K.; Kirk, Michelle R.; Heiser, Axel; Janssen, Peter H.; Wedlock, D. Neil (Frontiers in Microbiology, 2022)
Methane is produced in the rumen of ruminant livestock by methanogens, accounting for approximately 14.5% of anthropogenic greenhouse gas emissions in terms of global warming potential. Rumen contains a diversity of methanogens species, and only a few of these have been cultured. Immunomagnetic capture technology (ICT) is a simple and effective method to capture and concentrate target organisms in samples containing complex microflora. We hypothesized that antibody-coated magnetic beads could be used to demonstrate antibody specificity and cross-reactivity to methanogens in rumen samples. Sheep polyclonal antibodies raised against four isolates of rumen dwelling methanogens, Methanobrevibacter ruminantium strain M1, Methanobrevibacter spp. AbM4, Methanobrevibacter spp. D5, and Methanobrevibacter spp. SM9 or an equal mix of antibodies to all four isolates, were used to coat paramagnetic beads. ICT was used together with flow cytometry and qPCR to optimize key parameters: the ratio of antibody to beads, coupling time between antibody and paramagnetic beads to produce immunomagnetic beads (IMBs), and optimal incubation time for the capture of methanogen cells by IMBs. Under optimized conditions, IMBs bound strongly to their respective isolates and showed a degree of cross-reactivity with isolates of other Methanobrevibacter spp. in buffer and in rumen fluid, and with resident methanogens in rumen content samples. The evidence provided here indicate that this method can be used to study the interaction of antibodies with antigens of rumen methanogens, to understand antigen cross-reactivity and antibody binding efficiency for the evaluation of antigens used for the development of a broad-spectrum anti-methanogen vaccine for the abatement of methane production.